Analisis Potensi Ekonomi Kebun Plasma Dalam Meningkatkan Kesejahteraan Masyarakat Ditinjau Dari Maqasyid Syariah: Studi Kasus di di Desa Kub. Tompek Kec. Batahan Kabupaten Mandailing Natal - Heldia Fitri; Maryam Batubara; Nurul Inayah (VISA: Journal of Vision and Ideas, 2023)
This study aims to find out what are the economic potentials of Plasma plantations and the level of community welfare in Kungan Tompek Village. The method used in this study is a qualitative approach, the data used are primary and secondary data. Data collection is done by interview, observation and documentation. And the research data was analyzed using analytical techniques consisting of data reduction, data display and verification. The results of this study are that there are three economic potentials of plasma plantations: Increasing income, Creating jobs, and Reducing unemployment. The economic potential of plasma plantations has been able to improve the welfare of the members of the plasma plantation community. Except for one informant whose welfare has not increased, that can be seen from the informant's inability to fulfill one of the five criteria for community welfare and also has not been able to improve the welfare of his community when viewed from the criteria for guarding religion and protecting the soul. Keywords: economic potential, community welfare, maqasyid sharia